TTCC-2019-02: real-world evidence of first-line cetuximab plus paclitaxel in recurrent or metastatic squamous cell carcinoma of the head and neck - Rubió-Casadevall, Jordi; Cirauqui Cirauqui, Beatriz; Martinez Trufero, Javier; Plana Serrahima, Maria; García Castaño, Almudena; Carral Maseda, Alberto; Iglesias Docampo, Lara; Pérez Segura, Pedro; Ceballos Lenza, Isaac; Gutiérrez Calderón, Vanesa; Fuster Salvà, José; Pena Álvarez, Carolina; et al. (Frontiers in Oncology, 2023)
Objectives To confirm the efficacy of ERBITAX scheme (paclitaxel 80 mg/m2 weekly and cetuximab 400mg/m2 loading dose, and then 250 mg/m2 weekly) as first-line treatment for patients with recurrent/metastatic squamous cell carcinoma of the head and neck (SCCHN) who are medically unfit for cisplatin-based (PT) chemotherapy. Materials and Methods This retrospective, non-interventional study involved 16 centers in Spain. Inclusion criteria were to have started receiving ERBITAX regimen from January 2012 to December 2018, histologically confirmed SCCHN including oral cavity, oropharynx, hypopharynx, and larynx; age ≥18 years; platinum (PT) chemotherapy-ineligibility due to performance status, comorbidities, high accumulated dose of PT or PT refractoriness. Results 531 patients from 16 hospitals in Spain were enrolled. The median age was 66 years, 82.7% were male and 83.5% were current/former smokers. Patients were ineligible to receive PT due to ECOG 2 (50.3%), comorbidities (32%), PT cumulative dose ≥ 225 mg/m2 (10.5%), or PT refractoriness (7.2%). Response rate was 37.7%. Median duration of response was 5.6 months (95% CI: 4.4-6.6). With a median follow-up of 8.7 months (95% CI: 7.7-10.2), median PFS and OS were 4.5 months (95% CI: 3.9-5.0) and 8.9 months (95% CI: 7.8-10.3). Patients treated with immunotherapy after ERBITAX had better OS with a median of 29.8 months compared to 13.8 months for those who received other treatments. The most common grade ≥ 3 toxicities were acne-like rash in 36 patients (6.8%) and oral mucositis in 8 patients (1.5%). Five (0.9%) patients experienced grade ≥ 3 febrile neutropenia. Conclusion This study confirms the real-world efficacy and tolerability of ERBITAX as first-line treatment in recurrent/metastatic SCCHN when PT is not feasible. Immunotherapy after treatment with ERBITAX showed remarkable promising survival, despite potential selection bias.